СИСТЕМАТИЗАЦІЯ ВИДІВ АНДЕРРАЙТИНГУ В СТРАХУВАННІ - Водолазська, Оксана Анатоліївна (Науковий журнал «Світ фінансів», 2017)
Водолазська О. А. Систематизація видів андеррайтингу в страхуванні. На основі критичного аналізу існуючих вітчизняних і зарубіжних поглядів щодо видів андерайтингу узагальнено особливості стандартного та індивідуального андеррайтингу. Обґрунтовано доцільність упорядкування класифікаційних ознак андерайтингу та подано їх структуризацію за критеріями стандартності ризику, новизною ризику, рівнем прийняття рішення про страхування ризику, охоплення ризиків, підгалузі страхування, глибини андеррайтингу, рівня ризикованості об’єкта страхування, суб’єктного складу, рівня інтегрованості, масштабності діяльності страховика, стадії його життєвого циклу, джерела страхових виплат, витратності андерайтингу та горизонту страхування. Водолазская О. А. Систематизация видов андеррайтинга в страховании. На основе критического анализа существующих отечественных и зарубежных взглядов относительно видов андеррайтинга, обобщены особенности стандартного и индивидуального андеррайтинга. Обоснована целесообразность составления классификационных признаков андеррайтинга и представлена их структуризация по критериям стандартности риска, новизны риска, уровня принятия решения о страховании риска, охвата рисков, подотрасли страхования, глубины андеррайтинга, уровня риска объекта страхования, субъектного состава, уровня интегрированности, масштабности деятельности страховщика, стадии его жизненного цикла, источника страховых выплат, затратности андеррайтинга и горизонта страхования. Vodolazska O. Systematics of underwriting in insurance. Introduction. A comprehensive activity of the insurer to identify, assess risks and to select the best coverage is called “the underwriting”. The lack of comprehensive understanding of the features of underwriting and classification eliminates the possibility of fulluse of the entire palette of possible types of underwriting in the insurance business. Purpose. The purpose of the article is to systematize the scientific achievements of Ukrainian and foreign experts in the disclosure approaches to classification of underwriting in insurance and justification of the need to improve the existing approaches to the determination of specific structure of the underwriting in insurance. Methods On the basis of a critical analysis and synthesis of existing domestic and foreign views on species diversity underwriting the features of the standard and individual underwriting were highlighted. Standard underwriting conducted for mass types of insurance, under which the homogeneous and relatively simple objects (apartments, household goods, cars, etc.) are insured. Individual underwriting involves insurance or rejection of insurance of the claimed subject matter. It based on an assessment of individual inherent risks of a particular object. Individual underwriting held in order to create or adjust the terms of the insurance contract and to determine the individual tariff. Results. The additional criteria of underwriting classifications are: standardization of risk, originality of risk, the level of decision-making on risk insurance, coverage of risks, sub-sector of insurance, the depth of underwriting, level of risk of insurance object, subject structure, the level of integration, the scale of operations of the insurer, the stage of the life cycle of the insurer, a source of insurance payments, a cost of underwriting and the horizon of insurance. Conclusion The proposed classification of underwriting allows you to organize the set of its kinds in the insurance business, as well as take into account the specificity of each species in the formation of underwriting policy.